PERAN TEKNOLOGI DAN INOVASI DALAM PENCEGAHAN KEJAHATAN SKIMMING DI BANK - Jordan Hue; Yonky Pernando (JCOME, 2023)
Skimming crime is a serious threat to the banking sector around the world. These crimes include the theft of credit or debit card data through illegal devices installed in ATM machines or payment terminals. The impact is not only detrimental to customers, but also leads to significant financial losses for banks and related financial institutions. Customers suffer financial losses from the theft of their card data, while banks have to replace the stolen funds, face investigation costs, and maintain the affected reputation. Loss of customer confidence, loss of reputation, waste of time, and potential legal problems are also the impact of skimming crimes. The research aims to explore the role of technology and innovation in the prevention of skimming crime in banks. We identify the use of EMV chips, advanced monitoring devices, intelligent data analysis, and innovations in ATM engine design as preventive solutions. The research uses mixed methods that include literature studies, secondary data analysis, interviews, surveys, case studies, and field observations to understand the role of technology and innovation in skimming prevention practices. Research results show that technology and innovation play an important role in protecting customers and bank finances from the threat of skimming. The use of EMV chips increases the security of transactions, stronger authentication protects cardholders, and innovations in the design of ATM machines reduce the risk of device manipulation by skimming perpetrators. Strong legal action is also required against the perpetrators who succeed in arresting. This research underlines the importance of sustainable investment in technology and innovation as part of a strategy to prevent skimming crime. By adopting state-of-the-art and continuously innovative technology solutions in device design, the banking sector can reduce the risk of harmful skimming crimes and protect the security of customers as well as banking industry's reputation.